A Mitochondrion‐Localized Two‐Photon Photosensitizer Generating Carbon Radicals Against Hypoxic Tumors. (3rd September 2020) - Kuang, Shi; Sun, Lingli; Zhang, Xianrui; Liao, Xinxing; Rees, Thomas W.; Zeng, Leli; Chen, Yu; Zhang, Xiting; Ji, Liangnian; Chao, Hui
Abstract: The efficacy of photodynamic therapy is typically reliant on the local concentration and diffusion of oxygen. Due to the hypoxic microenvironment found in solid tumors, oxygen‐independent photosensitizers are in great demand for cancer therapy. We herein report an iridium(III) anthraquinone complex as a mitochondrion‐localized carbon‐radical initiator. Its emission is turned on under hypoxic conditions after reduction by reductase. Furthermore, its two‐photon excitation properties ( λ ex =730 nm) are highly desirable for imaging. Upon irradiation, the reduced form of the complex generates carbon radicals, leading to a loss of mitochondrial membrane potential and cell death (IC50 light =2.1 μm, IC50 dark =58.2 μm, PI=27.7). The efficacy of the complex as a PDT agent was also demonstrated under hypoxic conditions in vivo. To the best of our knowledge, it is the first metal‐complex‐based theranostic agent which can generate carbon radicals for oxygen‐independent two‐photon photodynamic therapy. Abstract : A mitochondrion‐targeting iridium(III) anthraquinone complex is reported. It is selectively reduced under hypoxic conditions to generate strong turn‐on emission and carbon radicals, achieving in‐vitro and in‐vivo oxygen‐independent photodynamic therapy.